Organizational culture and its role in improving the quality of educational service at the university center Tindouf from the perspective of professors. - مصطفى, بياض; ياسين, عبد الله; احمد, دن (Journal of Economics and Administrative Sciences, 2020)
This paper examines the impact of the organizational culture prevailing at the university center, Ali KafiTindouf, on the quality of the educational service provided by the university center Ali KafiTindouf from the point of view of the teachers of the center. The questionnaire method was used to determine the effect between the variables studied, by the distribution of 33 questionnaires on a random sample of the study community.The study found that the organizational culture prevailing at the university center of Ali KafiTindouf contributed to reaching higher levels in the awareness and quality of the educational service provided by the teachers of the center.